2012
DOI: 10.3410/f1000research.1-40.v2
|View full text |Cite
|
Sign up to set email alerts
|

Local indigenous knowledge about some medicinal plants in and around Kakamega forest in western Kenya

Abstract: Discuss this article AbstractKakamega forest is Kenya's only rainforest and is distinguishably rich in biodiversity but threatened by agricultural encroachment and other forms of human activity. It is also one of Kenya's Important Bird Areas and a significant source of natural products to neighboring rural communities, such as medicinal plants, food, wood and other fibers. By using structured questionnaires for direct interviews, local indigenous knowledge was tapped through involvement of a focal group of eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
3
4
0
Order By: Relevance
“…However, this study observed that older TMPs were more recognized and possessed extensive knowledge about medicinal plants. This observation aligns with other studies conducted in various parts of Kakamega County (Mukungu et al 2016, Odongo et al 2018, Otieno & Analo 2012, Shiracko et al 2016. The majority of respondents were advanced in age, and close relatives, particularly parents and grandparents, were frequently mentioned as the primary sources of traditional knowledge.…”
Section: Transmission and Preservation Of Traditional Medicinal Knowl...supporting
confidence: 92%
See 1 more Smart Citation
“…However, this study observed that older TMPs were more recognized and possessed extensive knowledge about medicinal plants. This observation aligns with other studies conducted in various parts of Kakamega County (Mukungu et al 2016, Odongo et al 2018, Otieno & Analo 2012, Shiracko et al 2016. The majority of respondents were advanced in age, and close relatives, particularly parents and grandparents, were frequently mentioned as the primary sources of traditional knowledge.…”
Section: Transmission and Preservation Of Traditional Medicinal Knowl...supporting
confidence: 92%
“…The majority (76.9%) of the herbal medicines were taken orally, 9.2% were used as eye, ear, and nose drops, and 4.6% were inhaled and swabbed. Because most plants are used to treat digestive or peptic, respiratory, or vector-borne illnesses, the oral route is generally used (Odongo et al 2018, Otieno et al 2012. On all the modes of preparation and administration recorded, regardless of the plant part(s) or mixtures utilized, water was the major medium for all medicinal preparations.…”
Section: Utilization Of Plant Parts and Conservation Considerationsmentioning
confidence: 99%
“…These include local uses such as fencing, building, firewood, timber, fodder, fruits, in addition to others such as boundary, brewing, broom, basketry, cleaning utensils, thatching, toiletry, gum arabica, making gutters, life fencing, mole traps, shade and walking sticks as well as for making soap. In Kenya, the plant resources provide important social and economic contribution to rural livelihoods (Otieno and Analo, 2012). The cultural uses of indigenous plants presented in the study are further supported by observations that the Marakwets use a great variety of wild species for a diverse range of purposes.…”
Section: Discussionsupporting
confidence: 65%
“…Oleaeceae, Gramineae, Anacardiaceae, Apiaceae, Aloeaceae, Salicaceae, and Polygonaceae the plant families of the retrieved plants. The reported species were Olea capensis also known as Olea europea [25] , Cymbopogon citratus, Heteromorpha trifoliate [26] , Mangifera indica L. [27], Bequartiodendron oblanceolata, Aloe elgonica, Dovyalis macrocalyx (Oliv.) Warb and Rumex usambarensis Jacq.…”
Section: Antiulcer Medicinal Plants Used By Luhya People Of Western Kenyamentioning
confidence: 99%
“…It is a dominant forest tree mostly known for shade. It's leaves are used tradionally for the treatment of ulcers [25] .…”
Section: Olea Capensis/ Olea Europeamentioning
confidence: 99%